Fibrous Dysplasia of the Palate: Report of a Case and Review of Palatal Swellings - Balasundari Shreedhar; Mala Kamboj; Nishant Kumar; Sameera Shamim Khan (Hindawi Limited, 2012)
Fibrous dysplasia is a benign fibroosseous lesion characterised by the replacement of normal bone by excessive proliferation of cellular fibrous connective tissue which is slowly replaced by bone, osteoid, or cementum-like material. It causes bone pain, deformities, and pathological fractures. Fibrous dysplasia (FD) is a sporadic benign skeletal disorder that can affect one bone (monostotic form) or multiple bones (polyostotic form). In this paper, we present case of a monostotic fibrous dysplasia on the hard palate of 14-year-old girl and a tabular review of common palatal swellings.